Engaging Knowledge Users with Mental Health Experience in a Mixed-Methods Systematic Review of Post-secondary Students with Psychosis: Reflections and Lessons Learned from a Master's Thesis - Victoria Sanderson; Amanda Vandyk; Jean Daniel Jacob; Ian D. Graham (Kerman University of Medical Sciences, 2022)
Engaging knowledge users (KUs) as research team members throughout the research process helps generate relevant knowledge and may improve uptake of research results. The purpose of this article is to describe how an integrated knowledge translation (iKT) approach was embedded within a master's thesis project comprising a mixed-methods systematic review. KUs were engaged in four distinct phases of the systematic review process, including (1) proposal development; (2) development of the research question and approach; (3) creation of an advisory panel; and (4) an end of study meeting to interpret findings and plan dissemination of findings. The extent of each KU's engagement on the research team fluctuated during the study. Challenges included maintaining the same KUs throughout the project and maintaining the scope of the project to align with a master's thesis. Our suggestions for optimizing graduate student iKT projects include having regular team meetings and periodically checking in with team members to encourage reflection on overall engagement and progress of the project. Overall, KUs helped create a research project designed to address their needs and provided input on how results might translate into implications for clinical practice, education, academic policy, and future research within their respective contexts.